SPESIFIKASI TES DIAGNOSTIK EJAAN DAN TANDA BACA BERBASIS HIGH ORDER THINKING SKILLS - Pratiwi, Mega; Fitriani, Yustina (Universitas Hamzanwadi, 2025)
The ability of students to apply correct spelling and punctuation remains relatively low, which may negatively impact the quality of critical thinking in academic writing. Therefore, a diagnostic test instrument is needed not only to assess their skills but also to promote higher-order thinking skills (HOTS) in order to strengthen their understanding and application of language rules more deeply. The aim of this study is to develop a guideline for the construction of a diagnostic test on spelling and punctuation based on HOTS. The method used is a six-stage literature study, consisting of: (1) problem identification, (2) literature search, (3) literature selection, (4) literature organization, (5) synthesis and critical analysis, and (6) writing the literature review results. The results of this study include: (1) the development of a diagnostic test on spelling, (2) the development of a diagnostic test on punctuation, (3) scoring techniques, and (4) feedback mechanisms. The scientific contributions of this research are: (1) a systematic development of diagnostic test specifications for spelling and punctuation, with an emphasis on the cognitive levels of HOTS (C4-analysis, C5-evaluation, C6-creation), (2) the direct integration of the Indonesian Spelling Guidelines with HOTS indicators, making the test not only normative but also reflective and productive, and (3) the combination of multiple-choice and open-ended (C6) question formats in one diagnostic system — in accordance with the principles of multiformat assessment.